Functional Foods for Replacing Chemical Filled Medicines: Functional Foods for Replacing Chemical Filled Medicines - Saini, Rummi Devi (International Journal of Pharmaceutical & Biological Archive, 2018)
Consumers have shifted from an emphasis on satisfying hunger and taste to an emphasis on the use of food to promote their physical and mental health and to reduce the disease risk during the past two decades. People believe that eating the right food i.e. Functional food will increase their life. The change in consumer’s attitude towards food is mainly due to increased health care costs, desire to enhance personal health, advances scientific evidence that diet can reduce diseases risk etc. In this review a variety of functional foods are categorized according to this type of evidence supporting their chemical composition, functionality and recommended intakes. Their applications for controlling various diseases without using chemical filled medicines are also discussed. The safety concerns of functional foods are also raised.